1991
DOI: 10.1128/jvi.65.1.195-205.1991
|View full text |Cite
|
Sign up to set email alerts
|

The three major immediate-early transcripts of bovine herpesvirus 1 arise from two divergent and spliced transcription units

Abstract: Among 54 transcripts expressed in a temporal cascade during lytic infection with bovine herpesvirus 1, we have previously identified three major immediate-early (IE) RNAs, IER4.2 (4.2 kb), IER2.9 (2.9 kb), and IER1.7 (1.6 to 1.8 kb depending on the virus strain) transcribed from the HindlIl C genome region (U. V.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
72
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(75 citation statements)
references
References 72 publications
3
72
0
Order By: Relevance
“…To date, bICP0 is the only known BHV-1 encoded protein that can interfere with IFN dependent transcription in transient transfection assays (Henderson et al, 2005;Jones and Chowdhury, 2009;Saira et al, 2007;Saira and Jones, 2009). bICP0 mRNA is an IE and E transcript (Wirth et al, 1992;Wirth et al, 1989;Wirth et al, 1991), and thus bICP0 protein expression is not affected when infected cells are treated with PAA (data not shown). In general, these studies suggested that binding of the BHV-1 virion and/or viral entry induced IFN-β RNA expression in low passage BK cells.…”
Section: Discussionmentioning
confidence: 93%
“…To date, bICP0 is the only known BHV-1 encoded protein that can interfere with IFN dependent transcription in transient transfection assays (Henderson et al, 2005;Jones and Chowdhury, 2009;Saira et al, 2007;Saira and Jones, 2009). bICP0 mRNA is an IE and E transcript (Wirth et al, 1992;Wirth et al, 1989;Wirth et al, 1991), and thus bICP0 protein expression is not affected when infected cells are treated with PAA (data not shown). In general, these studies suggested that binding of the BHV-1 virion and/or viral entry induced IFN-β RNA expression in low passage BK cells.…”
Section: Discussionmentioning
confidence: 93%
“…Positions of immediate-early transcripts and LR transcript are shown (arrows). IE 2.9 is the 2.9-kb immediate-early transcript derived from IEtu1, and E 2.6 is the 2.6-kb early transcript (26,27). IE 2.9 and E 2.6 are translated into identical proteins which have transcriptional transacting activity; the position of the stop codon (F) is indicated.…”
Section: Immunodetection Of 41-kda Protein In Bhv-1-infected Bt Cellsmentioning
confidence: 99%
“…In contrast, in the alphaherpesviruses, IE genes are located within repeated regions of the genome or in unique sequences adjacent to the repeats. IE genes have been mapped to repeat regions in the alphaherpesviruses herpes simplex virus type 1, bovine herpesvirus 1, varicella-zoster virus, equine herpesvirus 1, and pseudorabies virus (2,6,7,12,16,26,37). The position of the IE genes in the CCV genome, along with the short replication cycle and rapid destruction of cells in tissue culture (25), suggests that CCV is more closely related to the alphaherpesviruses than to other subfamilies of herpesviruses.…”
mentioning
confidence: 99%